2006
DOI: 10.1097/01.ico.0000164782.10667.ed
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Effects of Fluoroquinolone and Aminoglycoside Antibiotics on Human Keratocytes

Abstract: Relative effects of aminoglycosides and fluoroquinolones on stromal keratocytes appear to be different: netilmicin was shown to be significantly less toxic than ofloxacin. This finding is particularly relevant in deciding the optimal antibiotic to be applied in clinical situations in which the epithelium is absent or compromised, as after photorefractive keratectomy, alkali burns, or ulcerative keratitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 30 publications
0
4
0
1
Order By: Relevance
“…Some earlier studies compared the cytotoxicity between FQs, ofloxacin and the aminoglycoside, netilmicin. [35][36][37] They concluded that netilmicin was significantly less toxic than ofloxacin to human keratocytes, 37 to intact and mechanically damaged rabbit eyes, 36 and to rabbit corneal epithelial cells. 35 Mallari et al 38 also found an increased risk of corneal perforation after FQ treatment for bacterial keratitis, compared with treatment with fortified antibiotics (cephazolin 5% and tobramycin 1.36%).In our study, preservative-free fortified gentamicin and cefazolin were less cytotoxic to corneal epithelium cells than all the other FQ solutions tested.…”
Section: Discussionmentioning
confidence: 99%
“…Some earlier studies compared the cytotoxicity between FQs, ofloxacin and the aminoglycoside, netilmicin. [35][36][37] They concluded that netilmicin was significantly less toxic than ofloxacin to human keratocytes, 37 to intact and mechanically damaged rabbit eyes, 36 and to rabbit corneal epithelial cells. 35 Mallari et al 38 also found an increased risk of corneal perforation after FQ treatment for bacterial keratitis, compared with treatment with fortified antibiotics (cephazolin 5% and tobramycin 1.36%).In our study, preservative-free fortified gentamicin and cefazolin were less cytotoxic to corneal epithelium cells than all the other FQ solutions tested.…”
Section: Discussionmentioning
confidence: 99%
“…Netilmicin is a broad spectrum, third generation aminoglycoside with excellent in vitro activity against the most common bacterial ocular pathogens, including Pseudomonas spp 14,2729. Netilmicin is noncytotoxic and does not interfere with physiological healing, and is therefore able to provide good protection against bacterial infections during the wound repair process 12,13,15…”
Section: Discussionmentioning
confidence: 99%
“…This gel has no preservative and contains two natural biopolymers (xanthan gum and sodium hyaluronate) in addition to netilmicin. Hyaluronate is well known for promoting physiological wound healing by stimulating corneal epithelial cell migration and proliferation,911 whereas netilmicin is an effective, safe, and noncytotoxic antibiotic that is able to provide good protection against bacterial infections during the process of wound repair 1215…”
mentioning
confidence: 99%
“…26 Topically applied fluoroquinolones have been considered to be more toxic to the corneal epithelium than other antibiotic agents. 27,28 However, in a recently published study levofloxacin did not negatively influence epithelial wound healing. 29 Moreover, levofloxacin was shown to be less cytotoxic on human corneal keratocytes and epithelial cells than other fluoroquinolones, including gatifloxacin, moxifloxacin, ciprofloxacin and ofloxacin.…”
Section: Pharmacokinetic and Toxicological Propertiesmentioning
confidence: 92%